2004
DOI: 10.1207/s15324796abm2801_8
|View full text |Cite
|
Sign up to set email alerts
|

Job characteristics, occupational status, and ambulatory cardiovascular activity in women

Abstract: Inasmuch as ambulatory SBP and HR predict future cardiovascular morbidity and mortality, women with both lower status occupations and stressful job circumstances could be at disproportionately high cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…28,29 In a number of studies, job stress measures were related to systolic ambulatory BP whereas no association was found with diastolic BP. 22,[43][44][45] High job strain within our population resulted in significant elevations in both systolic and diastolic BP, although the associations with diastolic BP were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 In a number of studies, job stress measures were related to systolic ambulatory BP whereas no association was found with diastolic BP. 22,[43][44][45] High job strain within our population resulted in significant elevations in both systolic and diastolic BP, although the associations with diastolic BP were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are some studies which showed a link between psychological stress, anxiety and depression about women's workplace conditions [7,8]. It has been shown that stressful working conditions have an association with both mental and physical diseases in the case of women [9]. Quality of life (QoL) is one of the most important aspects of mental health.…”
Section: Measurement and Toolsmentioning
confidence: 99%
“…Job strain and low decision latitude have also been associated with decreased HF (e.g. Gallo, Bogart, Vranceanu & Wait, 2004;Collins, Karasek & Costas, 2005).…”
Section: Index Termsmentioning
confidence: 99%
“…Job strain and low decision latitude have also been associated with decreased HF (e.g. Gallo, Bogart, Vranceanu & Wait, 2004;Collins, Karasek & Costas, 2005).Several studies have shown that behavioral procedures that increase blood pressure and heart rate acutely also alter HRV consistent with decreases in parasympathetic activity (Madden & Savard, 1995;Reims et al, 2005;Guasti et al, 2005). In addition, decreases in HF of (Falkner & Kushner, 1990) found that mental stress generated larger increases in blood pressure and heart rate in SS than SI subjects.…”
mentioning
confidence: 99%